Penerapan model pembelajaran PBL terintegrasi STEM untuk meningkatkan aktivitas dan hasil belajar peserta didik di kelas XII IPA 5 SMAN 7 Padang - Sri Indrawati Prihatin Ningsih (Universitas Negeri Padang, 2020)
The purpose of this study was to increase the activities and learning outcomes of physics in class XII IPA 5 SMAN 7 Padang, using an integrated Problem Based Learning (PBL) learning model of Science Technology Engineering and Mathematics (STEM). The method used is classroom action research, which consists of two cycles. The data collection instrument used observation sheets and test learning outcomes. Observation data were processed using percentage techniques and graphical analysis, while student learning outcomes were processed using descriptive statistics. Based on the results of data analysis, it can be concluded that the use of STEM integrated PBL learning models can increase the activity and learning outcomes of students.